La (re)lecture écopoétique de l’Œuvre de Maurice Genevoix - Quéméneur, Anne Hélène (Verbum – Analecta Neolatina, 2025)
We analyze the work of the French writer Maurice Genevoix (1880–1980) and we don’t only approach the First World War as a starting point in all of his work, but in the same way we establish the dichotomy between what represented the conflict of war and the inherent presence of nature as a concrete and symbolic reality. We base the methodology developed by the researcher Pierre Schoentjes about the ecopoetic dimension. We want to highlight that this unmissable author received the Goncourt prize in 1925: he was also a French academician and his prestige found new momentum from November 11, 2020 thanks to the ceremony of his pantheonization in France. This significant fact undoubtedly pushes us to reread his work, symbol of a war literature (lived and written on the front line); we have to admit that he was a great precursor of the ecopoetic movement: the environmental literature currently in vogue within the French-speaking literary world.